Criminalistics and Forensic Sciences: Problems of Differentiation and Integration - R. L. Stepaniuk; T. P. Matiushkova (Bulletin of Kharkiv National University of Internal Affairs)
The authors have clarified perspectives for further development of criminalistics in Ukraine under the influence of integration processes of this science from Forensic Science. The genesis of the national model of criminalistics has been briefly studied; a comparative analysis of its content with Forensic Science has been accomplished; and the ways of further development of the system of criminalistics and related sciences in Ukraine have been defined considering the global tendencies of convergence of different models of this field of scientific knowledge. It has been emphasized that the use of the terms of “Criminalistics”, “Forensic Sciences” and “Criminal Investigation” is explained not just by the specifics of terminology in different countries, but primarily due to differences in defining the nature and internal content of these disciplines. According to the authors, the integration of tactical and technical criminalistics tools and methods of combating crime is quite acceptable and not only significantly enriches the arsenal of criminalistics, but determines its existence as an independent science. Such an approach allows us to consider criminalistics not just as one of the many sections of Forensic Sciences, but to single out it as one of the most comprehensive sciences that integrates all other forensic disciplines. The domestic model of criminalistics, in contrast to Forensic Science, represents the issues of a legal nature (criminalistics tactics and methodology), which makes it a science of dual (synthetic) nature. The integration processes observed in the development of criminalistics and Forensic Science are gradually leading to the convergence of these sciences in content. Given this, it is impractical to take further steps to disintegrate criminalistics in Ukraine by separating forensic expertise into a separate science. Otherwise, there will be a complete depletion of the natural and technical component of criminalistics, which may result in the disappearance of this science in general.